CROP YEAR EFFECTS ON SEED YIELDS, GROWING CYCLE LENGTH, AND CHEMICAL COMPOSITION OF CHIA (SALVIA HISPANICA L) GROWING IN ECUADOR AND BOLIVIA - Ayerza, Ricardo (Emirates Journal of Food and Agriculture, 2017)
Chia (Salvia hispanica L.) is an annual summer herb, and a member of the Lamiaceae family. The present study was conducted between 2007-2010 period, on seeds commercially grown in Bolivia (Sub-Humid Chaco Ecosystem) and Ecuador (Tropical Forest Ecosystem). The crop year effect on the growing cycle length, seed yield, seed’s protein content, lipid content, and fatty acids profile, was determined. The mean growing cycle length ranged from 108-d at Sub-Humid Chaco Ecosystem to 113-d at the Tropical Forest Ecosystem. The Tropical Forest Ecosystem had higher maximum and average yields at each year crop, than the Sub-Humid Chaco Ecosystem. Overall, the seed from the Tropical Forest Ecosystem showed significant (P<0.05) higher content of alpha-linolenic fatty acid comparing to that from the Sub-Humid Chaco Ecosystem. The seeds from the Tropical Forest Ecosystem showed the lowest significant (P<0.05) linoleic and oleic fatty acid concentrations. The n-6:n-3 ratio was significantly (P<0.05) lower in oils from seeds grown in Ecuador compared to that of seeds grown in Bolivia. Regression analysis were performed for alpha-linolenic vs. oleic and linoleic fatty acid contents. Analysis using combined data of fatty acids from all four years and from both ecosystems revealed that alpha-linolenic fatty acid content was negatively correlated with its precursors –oleic (R2= 0.77, P < 0.0005), and linoleic (R2= 0.92, P < 0.0005) fatty acids. Compared to chia seeds grown in Bolivia, the chia seeds grown in Ecuador showed more stability and a significant (P<0.05) higher alpha-linolenic fatty acid content.